HUBUNGAN ANTARA KEBIASAAN MEROKOK DENGAN KESEHATAN RONGGA ORAL PADA MASYARAKAT BENTANGAN WONOSARI KLATEN - Wiwin Winarni; Agil Melina (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2016)
Background Smoking has been widespreads to all group of societies andbecomes increased dramatically, especially children and teenager. This conditionis caused by the rising of force of the mass media to advertise the cigaretteproducts. The total number of smoker in Indonesia has been increaseddramatically. Study conducted by Tobacco Atlas in 2009 showed that Indonesiagot number five for the country with large smoker population all over the world.Purpose to analyze the correlation between smoking and health of cavity oral ofpeoples in Bentangan Wonosari Klaten.Methode This research used analytic with correlation design. The totalrespondens involved in this research were 40 peoples. Data was collected byusing quessionaires and observing the oral cavity of the respondens using OralHygiene Index . The data was analyzed by using chi square statistic.Result 1) Respondens with mild category is 32,5%, moderate 20%, severe 35%and very severe 12,5%. 2) The total number of respondens who suffered fromoral health disorder 27,5% and responden with healthy cavity oral 72,5%.Conclusion The variable of smoking has related to peoples oral health conditionin Bentangan Wonosari Klaten (p=0,002)Keywords : smoking, health of oral cavity